ANALISIS PERBANDINGAN RETURN ON ASSET DAN ECONOMIC VALUE ADDED PADA BANK KONVENSIONAL DAN BANK SYARIAH - Arsita, Delia; Diana, Nana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.07.TAHUN.2021, 2021)
Business competition in the banking world is getting tighter, this is what requires banks to maintain their financial performance. The purpose of this study is to compare the financial performance using the measurement of Return On Asset (ROA) and Economic Value Added   (EVA) in Conventional Banks and Islamic Banks during the period 2015 - 2019. This study used a comparative method with a quantitative descriptive approach and Secondary data obtained from the internet through the official website of the respective banks that were sampled through a purposive sampling method.. The results of this study indicate that there is a significant difference in the assessment of financial performance by measuring ROA and EVA in Conventional Banks and Islamic Banks. The financial performance of Islamic Banks is considered to be better based on ROA and EVA measurement. Overall, the measurement of EVA is considered better because this measurement can reflect the true value of the company by taking into account the risk of the bank that includes the cost of capital. Future research is suggested to add bank data samples, expand the research period, and also to add other measurements to get more accurate results.